(untitled) (Journal of Green Physiology, Genetics and Genomics, 2015)
Drought stress is one of the main abiotic constraints for wheat. Water deficit stress especially at early developmental stage affects forthcoming physiological and morphological attributes of wheat and considerably lessens overall performance of wheat. Breeding for drought stress tolerance can be possible with the help of conventional breeding tools. There is a dire need to notify water deficit stress tolerant germplasm which perform better under drought conditions. Fifty wheat genotypes were screened for drought tolerance when evaluated for three physiological and three morphological attributes. Out of all the studied attributes and genotypes, ETAD232, ETAD19 and ETAD211, shoot length, seedling length, root shoot ratio and relative water contents contributed more towards diversity. These genotypes and attributes could be exploited for drought tolerance wheat breeding programs.